2017
DOI: 10.3390/ijms18040741
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Metabolism and Its Role in the Development of Inflammatory Bowel Disease

Abstract: Beyond their role as structural molecules, sphingolipids are involved in many important cellular processes including cell proliferation, apoptosis, inflammation, and migration. Altered sphingolipid metabolism is observed in many pathological conditions including gastrointestinal diseases. Inflammatory bowel disease (IBD) represents a state of complex, unpredictable, and destructive inflammation of unknown origin within the gastrointestinal tract. The mechanisms explaining the pathophysiology of IBD involve sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 107 publications
(141 reference statements)
0
34
0
Order By: Relevance
“…In patients with inflammatory bowel disease (IBD), the risk of cancer is increased some 20-30-fold [52]. S1P is thought to be involved in the progression from IBD to cancer [53]. It may be that two homologous proteins (S1PL2021 and S1PL2025), which were recently reported in the pathogenic bacterium Burkholderia pseudomallei K96243, degrade host sphingolipids (SLs) via a mechanism mediated by the pyridoxal 5 0 -phosphate (PLP)dependent enzyme S1P lyase (S1PL) [54].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…In patients with inflammatory bowel disease (IBD), the risk of cancer is increased some 20-30-fold [52]. S1P is thought to be involved in the progression from IBD to cancer [53]. It may be that two homologous proteins (S1PL2021 and S1PL2025), which were recently reported in the pathogenic bacterium Burkholderia pseudomallei K96243, degrade host sphingolipids (SLs) via a mechanism mediated by the pyridoxal 5 0 -phosphate (PLP)dependent enzyme S1P lyase (S1PL) [54].…”
Section: Pathogenic Stimulusmentioning
confidence: 99%
“…Sphingosine metabolites are bioactive signaling lipids involved in many essential biological responses 1,2 . Several researchers have reported that sphingosine metabolites, such as sphingosine-1-phosphate (S1P) and phytos phingosine-1-phosphate (P1P), exert various physiological roles, including cell proliferation, differen tiation, migration, immunomodulation, metabolism, and survival [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelin, cholesterol, and other phospholipids are important components in the cell membrane, and their most pivotal function is acting as bioactive signaling molecules. Among them, sphingosine-1-phosphate (S1P) produced by sphingomyelin, is not only used as intracellular second messengers to regulated the cell cycle, but also binds to the specific receptors on the cell surface to modulate cell proliferation, apoptosis, invasion, migration, and adhesion molecule expression [ 12 14 ]. In addition, S1P can promote the survival of many cell types and simultaneously inhibit its apoptosis, and the biological effect mediated by S1P is closely correlated with tumor formation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%